Genome-Wide Identification and Evolutionary Analysis of Gossypium Tubby-Like Protein (TLP) Gene Family and Expression Analyses During Salt and Drought Stress - Bano, Nasreen; Fakhrah, Shafquat; Mohanty, Chandra Sekhar; Bag, Sumit Kumar (Frontiers in Plant Science, 2021)
Tubby-like proteins (TLPs) possess a highly conserved closed β barrel tubby domain at C-terminal and N-terminal F-box. The role of TLP gene family members has been widely discussed in numerous organisms; however, the detailed genome-wide study of this gene family in Gossypium species has not been reported till date. Here, we systematically identified 105 TLP gene family members in cotton (Gossypium arboreum, Gossypium raimondii, Gossypium hirsutum, and Gossypium barbadense) genomes and classified them into eight phylogenetic groups. Cotton TLP12 gene family members clustered into two groups, 4 and 8. They experienced higher evolutionary pressure in comparison to others, indicating the faster evolution in both diploid as well as in tetraploid cotton. Cotton TLP gene family members expanded mainly due to segmental duplication, while only one pair of tandem duplication was found in cotton TLPs paralogous gene pairs. Subsequent qRT-PCR validation of seven putative key candidate genes of GhTLPs indicated that GhTLP11A and GhTLP12A.1 genes were highly sensitive toward salt and drought stress. The co-expression network, pathways and cis-regulatory elements of GhTLP11A and GhTLP12A.1 genes confirmed their functional importance in salt and drought stress responses. This study proposes the significance of GhTLP11A and GhTLP12A.1 genes in exerting control over salt and drought stress responses in G. hirsutum and also provides a reference for future research elaborating the biological roles of G. hirsutum TLPs in both stress responses.